The polycystic ovary syndrome : a comparison of the presentation in adolescents compared to women aged 35 years and older attending the Gynaecological Endocrine clinic at Groote Schuur Hospital - Morrison, Candice Jane (Department of Obstetrics and Gynaecology, 2015)
PCOS is the commonest endocrinopathy occurring in women of reproductive age. This study aimed at comparing the presentation of adolescents to that of women â‰¥ 35 years presenting to the gynaecological endocrine clinic with a diagnosis of PCOS. This was a descriptive cohort study. Since 1996 all women with PCOS have their clinical, metabolic and endocrine data entered into a database. We compared the initial presentation of adolescents and women aged 35 and above.